Comparing the body to superior others: Associations with daily exercise and body evaluation in men and women. (November 2016) - Pila, Eva; Barlow, Meaghan A.; Wrosch, Carsten; Sabiston, Catherine M.
Abstract: Objectives: This study tested the link between daily body-related upward social comparisons (BUSCs) and exercise behavior, and examined how appearance evaluation and gender may impact this association. Method: In a weeklong assessment, 87 participants (54% women) completed daily retrospective measures of social comparisons and exercise behavior, and a one-time trait measure of appearance evaluation. Results: Based on findings from hierarchical linear modeling, men with more negative appearance evaluations reported higher exercise engagement on days when they made more (compared to less) BUSCs. Meanwhile, women with more negative appearance evaluations reported less exercise engagement on days when they engaged in more (compared to less) BUSCs. Conclusions: Among individuals who experience negative appearance evaluations, upward body comparisons are associated with more exercising among men, and lower exercise among women. BUSCs have an important role in promoting adaptive exercise behaviors and managing negative body image. Highlights: Men with poorer body image exercise more when they make more body comparisons. Women with poorer body image exercise less when they make more body comparisons. Upward comparisons may function to motivate men, and demotivate women to exercise.